Combined Pre- and Postnatal Minimally Invasive Approach to Complicated Pulmonary Sequestrations - Ichino, Martina (European J Pediatr Surg Rep, 2020)
Pulmonary sequestration (PS) is mostly asymptomatic but there is a proportion of fetuses that develop hydrops, leading to fetal or neonatal death. Fetal treatments are available, but postnatal management of the residual lesions is not uniformly defined. We present two cases of combined pre- and postnatal minimally invasive approach to complicated extra-lobar PS. Patient 1 presented with complicated PS at 31 weeks of gestation. Ultrasound-guided laser coagulation of the anomalous artery was successful. The patient was born asymptomatic at 38 weeks. Neonatal magnetic resonance imaging (MRI) showed a residual mass, confirmed by computed tomography (CT) at 6 months. No systemic artery was described, but perfusion was present. We decided for thoracoscopic resection. A residual artery was identified and sealed. Patient 2 presented with complicated PS at 25 weeks of gestation, underwent laser coagulation of the anomalous artery and was born asymptomatic at 38 weeks. Neonatal MRI showed persistence of the lesion, confirmed by CT scan at 4 months. We proceeded with thoracoscopic resection. A residual vessel was ligated. The patients 1 and 2 are now 24 and 21 months old, respectively, and healthy. Prenatal treatment of complicated PS is a life-saving procedure. Postnatal thoracoscopic resection of the residual lesion is feasible and safe; we believe it is the best course of treatment to grant the complete excision of the malformation.